The Effectiveness of Jigsaw Cooperative Learning Model on Students' Appreciation of Biodiversity at Senior High School SMA Negeri 1 Rantau Utara - Nur Safrani Siregar; Hasmi Syahputra Harahap; Khairul Khairul (Universitas Labuhanbatu, 2025)
The low appreciation and understanding of students towards biodiversity, especially medicinal plants, pose challenges in biology education in Indonesia. Traditional teacher-centered methods emphasize memorization and lack a local cultural context. This study examines the effectiveness of the Jigsaw cooperative learning model based on ethnoscience in improving students’ appreciation and understanding of medicinal plant biodiversity. A quasi-experimental design with a non-equivalent control group was used, involving grade X students of SMA Negeri 1 Rantau Utara. The experimental group used the Jigsaw model, while the control group followed conventional methods. Instruments included a Likert scale for appreciation and a multiple-choice test for understanding. Data analysis with SPSS 22.0 showed an average appreciation score of 67.03 and an understanding score of 87.66. The effectiveness test yielded a significance value of 0.000 (P < 0.005), indicating a significant improvement in the experimental group. The study concludes that the Jigsaw model enhances student engagement and appreciation of local knowledge, making it a relevant and contextual learning approach for strengthening students’ understanding of Indonesia’s natural and cultural heritage